The effect of nonlinear interactions between UFKW and Q16DW on the ionosphere - Ruidi Sun; Sheng-Yang Gu; Liuguan Ding; Yusong Qin; Min Jiang; Xiaodan Liu; Qiang Wang (Advances in Space Research, 2026)

Structural advantages of [B8O10(OH)6] for sustainable dual-functional scale/corrosion Inhibition in circulating water systems - Dong Guo; Ruidi Sun; Yahui Zhao; Yuansheng Pei; Li'an Hou (Desalination, 2026)

Unveiling the impact of 2D/3D urban morphology on thermal comfort across urban-rural gradients using machine learning - Chunguang Hu; Yuxuan Tao; Maomao Zhang; Houbao Fan; Nan Xu; Yucheng Sun; Ruidi Yuan; Jianqing Zhao (Energy and Buildings, 2025)

Assessment of the gridded burden of disease caused by PM2.5-bound heavy metals in Beijing based on machine learning algorithm and DALYs - Tong Lyu; Xin Meng; Yilin Tang; Yidan Zhang; Yue Gao; Wei Zhang; Xu Zhou; Ruidi Zhang; Yue Sun; Siqi Liu; Tianqing Guo; Jianan Zhou; et al. (Science of The Total Environment, 2025)

The Role of MicroRNA-206 in the Regulation of Diabetic Wound Healing via Hypoxia-Inducible Factor 1-Alpha - Zeming Bai; Dapeng Zhou; Kai Tao; Feng Lin; Hongyi Wang; Haiwei Sun; Ruidi Liu; Zhe Li (Biochemical Genetics, 2025)
Successful wound healing in diabetic patients is hindered by dysregulated miRNA expression. This study aimed to investigate the abnormal expression of miRNAs in diabetic wound healing and the potential therapeutic role of modulating the miR-206/HIF-1α pathway. MicroRNA assays were used to identify differentially expressed miRNAs in diabetic wound sites and adjacent areas. In vitro models and a rat diabetic model were established to evaluate the effects of miR-206 on HIF-1α regulation and wound healing. The study revealed differential expression of miR-206 in diabetic wound tissues, its interaction with HIF-1α, and the inhibitory effect of miR-206 on cell growth under high glucose conditions. Modulating the miR-206/HIF-1α pathway using miR-206 antagomir promoted HIF-1α, CD34, and VEGF expression, ultimately enhancing diabetic wound healing.